(untitled) (Bangladesh Journal of Botany, 2024)
The experiment was conducted at an experimental farm to find out the optimum set size and suitable planting date of onion during kharif season for obtaining the maximum yield. The trials had three replications and 16 treatment combinations on Agrifound Dark Red. The treatments included four set sizes (small 1-1.5cm, medium 1.5-2.0cm, large 2.0-2.5cm, and extra large >2.5cm) and four planting dates (July 10, July 25, August 10, and August 25). The treatment combination of 1.5-2.0cm set size and 10th August planting was advantageous for several characteristics. Small sets (1-1.5 cm) produced small bulbs and also the yield was reduced. Large and exceptionally large size sets (2.0-2.5cm and >2.5cm) produced more twins, triplets, split bulbs, and bolting, which were undesirable features. Considering net profit and economic yields, medium set size and planting on August 10th was found to be more profitable (1: 3.84). Bangladesh J. Bot. 53(1): 17-23, 2024 (March)